Analisis Kerusakan Dan Penanganan Jalan Menggunakan Metode Bina Marga Pada Ruas Jalan Poros Pare-Pare - Sidrap Di Kabupaten Sidrap - Syahrul, Syahlendra; Kushari, Kushari; Setiabudhi, Indrasurya; Nur Azizah MS, Andi Chairun; Amalia, Kiki Rezki (Politeknik Negeri Ujung Pandang, 2024)
This study was conducted to understand the condition of traffic characteristics, types of road damage, the value of road conditions, and handling road damage on the Pare-pare - Sidrap Axis road section in Sidrap Regency KM 177+000 to KM 178+000. Meanwhile, the method used in this study is the Highways method. This method reviews the volume of traffic and the type of damage that occurs on the road pavement visually with the final result in the form of a road condition value which will later be an alternative solution in repairing road damage at the research site. The results of the study were in the form of the value of traffic characteristics on the pare-pare - sidrap axis road section in Sidrap Regency for STA 0 + 000 - 1 + 000 which obtained the average speed value of all vehicles on the right and left lanes of 34.74 km / h and 35.03 km / h respectively with an LHR volume value of 8630.675 SMP / Day. Meanwhile, the types of road damage found at the study site are longitudinal cracks, random cracks, crocodile cracks, grooves, collapses, roughs, grain release, disintegration, and patches and potholes. With the value of road conditions in priority order 4 which is included in the category of periodic maintenance.